A case of perirenal non‐specific lymphadenitis mimicking a solitary renal mass. Issue 1 (9th September 2021) - Umeda, Shun; Hatano, Koji; Kato, Taigo; Kawashima, Atsunari; Abe, Toyofumi; Fukuhara, Shinichiro; Uemura, Motohide; Kiuchi, Hiroshi; Imamura, Ryoichi; Nonomura, Norio
Abstract : Introduction: Since the diagnosis of small renal masses is often a challenge despite improvements in imaging modalities, renal tumor biopsy provides useful information regarding treatment decisions. However, there is no established treatment strategy when renal biopsy shows lymphoid tissue. Case presentation: A 63‐year‐old woman was referred to our department for the investigation of a small renal mass. Contrast‐enhanced computed tomography showed a weakly enhancing mass 39 × 17 mm in diameter in the left kidney. A renal tumor biopsy was performed, and histopathological examination showed lymphoid tissue, but the diagnosis was not confirmed. The tumor was bluntly dissected from the renal capsule via robotic‐assisted laparoscopic surgery without renal artery clamping. The pathological diagnosis was non‐specific lymphadenitis. Conclusion: We report a rare case of perirenal non‐specific lymphadenitis mimicking a solitary renal mass. Non‐specific lymphadenitis is a possible differential diagnosis of renal masses.